COOPERATION IN FOREST FIRE FIGHTING IN THE BALKANS - Chakar, Ali (E-Journal VFU, 2025)
The Balkan region is highly vulnerable to the increasing frequency and intensity of forest fires due to climate change and ineffective land management practices. Regional cooperation is key to building resilience against this cross-border problem, focusing on strengthening prevention, preparedness and joint response. Initiatives such as cross-border cooperation programmes (EU Civil Protection Mechanism) facilitate knowledge exchange, training of volunteer and professional teams and development of common strategies and early warning systems. The aim is to improve operational capacity at national level and ensure coordinated, rapid and effective protection of human life, property and critical ecosystems across the region.